Biomarcadores de Efeito do Chorume da Lixeira Pública de Parintins-Am em tambaqui (Colossoma Macropomum) - Santos, Izabel Cristina Conceição dos (2012)
The aquatic biota is constantly exposed to a large number of toxic substances from several emission sources. Among the sources of water pollution, there is leachate. Leachate is a liquid highly toxic, resulting from the decomposition of waste, and represents an environmental problem of global scale. Even the most pristine areas are not free from this pressure. The city of Parintins-Am, for example, also has suffered the impact of such pollution. The aggravating fact this particular situation is that this region is surrounded by a number of bodies of water, for example, Lake Macurany. This is one of the main lakes that surround the island of Parintins, as being of vital importance to their preservation. Therefore, the quality of these environments can potentially being compromised by the discharge of leachate. The present study aimed to evaluate the effect of leachate from the public Parintins, on tambaqui, Colossoma macropomum (Cuvier, 1818), after 96h of exposure in the laboratory and after exposure for 24 and 48, in situ in Lake the Macurany. In both situations the hematological parameters, ionic, enzymatic and genotoxic effects were determined and evaluated for use as potential biomarkers of contamination by leachate. To evaluate the effect of leachate under laboratory exposure, we used 32 individuals of the species C. macropomum distributed in groups of 8 specimens exposed to individual tanks with a capacity of 6 liters, containing water slurry in three different dilutions (1:100, 1:1000 and 1:10,000) for a period of 96 hours of exposure. Another group of eight specimens were exposed only to well water, considered as the control group. The environmental impact assessment of the presence of toxic dumps in Lake Macurany was performed in situ by exposure of specimens of C. macropomum, in cages with a volume of 9L in two different exposure times, 24 and 48. Under the experimental conditions used were 30 individuals in group 3 specimens exposed at a point downstream of the trash, and another group of 30 subjects was exposed at a point upstream of the trash. The laboratory exposure resulted in anemia, as evidenced by the decrease in hemoglobin concentration, hematocrit and red blood cells count. Glucose levels increased in animals exposed to different concentrations of manure showing that these animals went through a period of stress. Plasma levels of Na+, K+ and Cl- also increased in the groups exposed to different concentrations of leachate, suggesting that the slurry can interfere with processes regulating ion in specimens of tambaqui. Exposure to the slurry caused severe liver damage assessed indirectly by increased concentration of alanine and aspartate aminotransferase and alkaline phosphatase. We also observed an increase in the levels of cholinesterase, suggesting disturbances in the transmission of nerve impulses in these animals. Increases in enzymatic parameters were proportional to the concentration of slurry, indicating a dose-dependent response. The results obtained by means of genotoxic parameters, comet assay and nuclear abnormalities, indicate that exposure to concentrations tested manure causes increased damage to genetic material and erythrocytic nuclear abnormalities. The in situ exposure in Lake Macurany downstream of Parintins-Am public trash, also triggered a series of changes in all parameters. For haematological parameters, decreased values of hematocrit and no significant difference in hemoglobin concentration, and the number of circulating red blood cells was increased only in the specimens exposed for 24 hours downstream to streamline the carrying of oxygen. The blood glucose concentration also increased in these animals, suggesting that the animals went through a period of stress. Plasma levels of Na+, K+ and Cl- and levels of enzymes ALT, AST, ALP and Che increased in specimens from the point downstream tip, showing again that the lake contamination is capable of triggering biochemical and physiological disturbances. The results for comet assay and nuclear abnormalities suggest genotoxicity for exposure in situ. Generally, exposure of C. macropomum to different concentrations of manure and contamination of Lake Macurany was sufficient to cause serious physiological and biochemical disturbances, thus compromising the health of this species. The results suggest that the hematological parameters, ionic, enzymatic, comet assay and erythrocytic nuclear abnormalities analyzed for the species Colossoma macropomum proved to be a potential biomarkers of contamination by leachate. Keywords: leachate; biomarkers; Colossoma macropomum; Parintins; Lake Macurany.